“It rejuvenates!” On the art of speech characterization in The Life of Arseniev - L. G. Panova (Шаги)
The Life of Arseniev has been studied insufficiently and one-sidedly. Although critics praised Ivan Bunin for his stylistically impeccable narrative manner, the novel’s linguistic aspect has never been the focus of analysis. Meanwhile, the protagonist of this Künstlerroman is a writer, whose maturation involves mastering literature and the Russian language in its many varieties. The Life of Arseniev is narrated by the same person but already fully matured. As a fifty-year-old author, Arseniev has learned the secrets of his profession and has become famous. Recollecting in emigration his early life, Arseniev documents the Russian language of the time of his youth, i.e. the turn of the 19th and 20th centuries, at the time of the writing being on the brink of extinction as the result of the new Soviet rule and control. In his capacity of Bunin’s alter ego, Arseniev creates vivid individual speech portraits of the characters (the article analyzes four of those) and one collective speech portrait (of Arseniev’s antagonists — the Socialist underground community). These portraits share the common pattern of reflecting the speakers’ personalities through their manner of speaking, while varying the specific techniques of linguistic portrayal. The article pays special attention to the exclamation “Zamolazhivaet!” [It rejuvenates!] used by Arseniev’s father in the course of his drinking sessions: the meaning of this word, the history of its appearance in dictionaries and memoirs, its metaphoric use by Bunin (and Arseniev), and the extent to which all this is reflected in the extant English, French, and German translations of the novel.